Analisis Dan Perancangan Aplikasi Pengelolaan Komunikasi Dan Informasi Pada Apotek Anisa Dengan Akses Client-Server Dan Virtual Host - Ricki Ardiansyah (Universitas Darussalam Gontor, 2017)
The The rapid development of science and technology has encouraged people to seek and implement new ways and methods in the process of work in order to run more easily and smoothly. By looking at the current technological sophistication, especially information and communication technology that can help facilitate the work of an organization or company that can be used as consideration in making a decision and provide timely and accurate information. So the author tries to take advantage of this to design an application Management Applications Communications And Information At Anisa Apotek as a tool to improve the effectiveness and accuracy of work, which during this process of data processing on Apotek anisa still done manually. With this application, it is expected Anisa Pharmacy can be more developed, so many customers who use it.